Putative Activation of the CB1 Cannabinoid Receptors Prevents Anxiety-Like Behavior, Oxidative Stress, and GABA Decrease in the Brain of Zebrafish Submitted to Acute Restraint Stress - Lucas Luz, Waldo; Santos-Silva, Mateus; Cardoso, Patrick Bruno; Assad, Nadyme; Moraes, Edinaldo Rogério da Silva; Grisólia, Alan Barroso Araújo; Braga, Danielle Valente; Leão, Luana Ketlen Reis; Moraes, Suellen Alessandra Soares de; Passos, Adelaide da Conceição; Batista, Evander de Jesus Oliveira; Gouveia, Amauri; et al. (Frontiers in Behavioral Neuroscience, 2021)
Anxiety disorder is a well-recognized condition observed in subjects submitted to acute stress. Although the brain mechanisms underlying this disorder remain unclear, the available evidence indicates that oxidative stress and GABAergic dysfunction mediate the generation of stress-induced anxiety. Cannabinoids are known to be efficient modulators of behavior, given that the activation of the cannabinoid receptors type-1 (CB1 receptors) induces anxiolytic-like effects in animal models. In the present study, we aimed to describe the effects of the stimulation of the CB1 receptors on anxiety-like behavior, oxidative stress, and the GABA content of the brains of zebrafish submitted to acute restraint stress (ARS). The animals submitted to the ARS protocol presented evident anxiety-like behavior with increased lipid peroxidation in the brain tissue. The evaluation of the levels of GABA in the zebrafish telencephalon presented decreased levels of GABA in the ARS group in comparison with the control. Treatment with ACEA, a specific CB1 receptor agonist, prevented ARS-induced anxiety-like behavior and oxidative stress in the zebrafish brain. ACEA treatment also prevented a decrease in GABA in the telencephalon of the animals submitted to the ARS protocol. Overall, these preclinical data strongly suggest that the CB1 receptors represent a potential target for development of the treatment of anxiety disorders elicited by acute stress.